Riding Two Horses At Once: Wither The Indian Navy? - Till, Geoffrey (2016)
The International Fleet Review recently held at the Indian port of VIshakhapatnam was a display of togetherness amongst the world's navies and at the same time a striking demonstration of India's naval aspirations. India's naval revival will be significant for the emerging strategic seascape in the Indo-Pacific area.